An investigation of the use of specific problem-solving strategies by mathematics teachers in lessons - Funda Aydın Güç; Dilay Daltaban (Journal of Pedagogical Research, 2021)
The aim of this study was to determine the strategies teachers offer to provide students with experience solving problems in the classroom. A total of 15 secondary school teachers serving in secondary schools were observed through 10 classes each, with no emphasis on the topics covered and grade levels taught. The researcher observing the classes performed a descriptive analysis of the problem-solving processes employed by the teachers through the lens of a series of known problem-solving strategies. The study revealed that the teachers employed a number of strategies as part of the problem-solving process. However, it was observed that the rate of application of strategies was rather low, even though specific strategies were nominally employed by the teachers. The study revealed that the strategy most frequently employed by the teachers during the problem-solving process was adopting a different point of view, while the strategy of making a drawing was also frequently applied. Moreover, the teachers employed the strategies of intelligent guessing and testing, working backwards, finding a pattern, solving a simpler analogous problem, and considering extreme cases, but with lesser frequency. On the other hand, the strategy of organizing data was not used by any of the teachers.